The Relationship Between the History of Providing Complementary Foods Under 6 Months and the Incidence of Stunting in Toddlers - Yulianti; Deviani Fatimah (JURNAL KEBIDANAN KESTRA (JKK), 2025)
The health and well-being of infants throughout their lives are significantly influenced by adequate nutrition. Nutritional deficiencies, often associated with stunting, can negatively impact a child's physical growth, motor development, and cognitive abilities. Infants who receive complementary foods (MPASI) before 6 months of age are at higher risk of experiencing essential nutrient deficiencies. This study aims to determine the relationship between the history of MPASI provision under 6 months of age and the incidence of stunting in toddlers in the Lumpue Community Health Center (Puskesmas) work area. The method used was a quantitative study with a cross-sectional design. The study population included all toddlers registered at the Lumpue Community Health Center in May 2025, totaling 97 children, with a sample size of 78 toddlers. The research instrument was a questionnaire, while data analysis used the chi-square test. The analysis results showed a p-value of 0.000, so the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Thus, there is a significant relationship between the provision of MPASI before 6 months of age and the incidence of stunting in toddlers. It is hoped that further research will be able to examine in more depth other factors such as the quality of complementary feeding, parenting patterns, and the role of health education in shaping the behavior of providing complementary feeding.